PELATIHAN PENGOLAHAN SUSU SAPI SEGAR DILEM WILIS - Anggi Martiningtyas; Arzendy Berlian Sabrina; Anggia Listyaningrum; Wina Rahman; Ikhvina Kurnia Dewi (Fakultas Pertanian, 2025)
Dilem Wilis is an area in Dompyong Village, Bendungan Subdistrict, Trenggalek Regency, which productively produces cow's milk, the main economic support for the community, especially local farmers. Fresh cow's milk is a liquid produced from cows' udders and contains a variety of essential nutrients for human consumption. However, high-yield fresh cow's milk cannot be stored for long periods. This training aims to enhance the skills of farmers and community members in the Wilis Valley area in processing fresh cow's milk into high-value economic products. Although the potential for dairy farming in this region is significant, most milk is still sold in its raw form at relatively low prices and with limited shelf life. The training method included theoretical material and hands-on practice (demonstrations and practical exercises) over two days. The core material covered sanitation and hygiene in milk handling, proper pasteurisation, and techniques for making various milk-based products such as sponge cake and milk candy. The training results showed a significant increase in participants' understanding of processed cow's milk products. Participants successfully produced marketable dairy product variants with a longer shelf life. This training is expected to create product diversification, open up new business opportunities, and directly increase the income and welfare of the Lembah Wilis community by increasing the selling value of their livestock products.